Language explication of the conceptualized meanings in ethno-cultural and socio-political aspects of discourse - Tameryan, Tatyana Yu.; Zheltukhina, Marina R.; Anikejeva, Irina G.; Arkhipenko, Natalia A.; Soboleva, Elena I.; Skuybedina, Olga Nikolaevna (Opción, 2020)
The study of ethnical concept language representations in the South Ossetia discourse as the discourse of not recognized country is a new direction in political linguistics. The article is focused on revealing verbal representations and cognitive features of the ethno specific political concept 'фæндаг'/'road' as the only highway connecting the Republic of South Ossetia – the State of Alania with the outside world through the Republic of North Ossetia (Russia). Based on lexicographic sources, media materials, Internet blogs and data from the associative experiment conducted in three age groups, among teenagers and young people, people of the middle and older generation, the structure and content of this discursive formation were revealed.